A Study of Emotionalism in Patients Undergoing Rehabilitation following Severe Acquired Brain Injury - Joanna McGrath (Behavioural Neurology)
The present study describes the phenomenon of emotionalism in a sample of brain injured patients of mixed aetiology, with a view to identifying issues relevant to clinical management, and possible causal factors. 82 subjects with severe acquired brain injury undergoing rehabilitation participated in a structured interview in which they were asked to report the presence/absence of emotionalism and degree of distress associated with it. Their overt crying behaviour was also observed and recorded. Independent variables that predicted crying during the interview were identified using a multiple logistic regression procedure. Prevalence rates of emotionalism-tearfulness were high in this sample (52% self-report, 36–41% Emotionalism-laughter was much less common (13%) Emotionalism-tearfulness was usually accompanied by negative affect, occurred in response to identifiable precipitants, and was often controllable. It was associated with major personal distress in about half the subjects who reported it. Independent variables which predicted crying behaviour were female gender and focal damage to the right cerebral hemisphere. It is concluded that an increased readiness to cry is common in people with severe acquired brain injury of mixed aetiology. The behaviour is meaningful, though not always distressing. The intensity of the behaviour is variable, and it may be most appropriate to regard emotionalism as a dimension rather than a syndrome. Implications for clinical management are discussed.